CD28/CTLA‐4/B7 costimulatory pathway blockade affects regulatory T‐cell function in autoimmunity. Issue 6 (3rd April 2015) - Vogel, Isabel; Kasran, Ahmad; Cremer, Jonathan; Kim, Yoo‐Jin; Boon, Louis; Van Gool, Stefaan W.; Ceuppens, Jan L.
<x xml:space="preserve">Abstract</x> Naïve T cells require B7/CD28 costimulation in order to be fully activated. Attempts to block this pathway have been effective in preventing unwanted immune reactions. As B7 blockade might also affect Treg cells and interfere with negative signaling through membrane CTLA‐4 on effector T (Teff) cells, its immune‐modulatory effects are potentially more complex. Here, we used the mouse model of multiple sclerosis (MS), EAE, to study the effect of B7 blockade. An effective therapy for MS patients has to interfere with ongoing inflammation, and therefore we injected CTLA‐4Ig at day 7 and 9 after immunization, when myelin‐reactive T cells have been primed and start migrating toward the CNS. Surprisingly, B7 blockade exacerbated disease signs and resulted in more severe CNS inflammation and demyelination, and was associated with an enhanced production of the inflammatory cytokines IL‐17 and IFN‐γ. Importantly, CTLA‐4Ig treatment resulted in a transient reduction of Ki67 and CTLA‐4 expression and function of peripheral Treg cells. Taken together, B7 blockade at a particular stage of the autoimmune response can result in the suppression of Treg cells, leading to a more severe disease.